2011
DOI: 10.1007/s12892-010-0035-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome organization in coffee as revealed by EST PCRRFLP, SNPs and SSR analysis

Abstract: An EST-based PCR-RFLP method was employed to gain insight into genome organization in eight allopolyploid Coffea arabica cultivars and seven diploid coffee species. The PCR-amplified products at 19 EST loci were digested with 46 different restriction enzymes and size fractioned in agarose gels. Most often, the sum of the fragments length was double or more than the PCR product. In arabica, this condition could be explained by assuming the presence of duplicated loci in paralogous chromosomes and this was suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 51 publications
(38 reference statements)
1
10
0
Order By: Relevance
“…Molecular markers allow direct access to the genome sequences and, thus, isolate the genetic variation of the environmental interferences (Ferrão et al 2007). The potential use of the Simple Sequence Repeats (SSR) and Inter-Simple Sequence Repeats (ISSR), microsatellite primers, has been demonstrated for Coffea related with genetic diversity of native species and germplasm bank accessions, geographical origin detection, domestication degree, coffee plant dispersion history, species identification and genealogy (Masumbuko and Bryngelsson 2006;LopezGartner et al 2009;Tshilenge et al 2009;Missio et al 2010;Setotaw et al 2010;Mishra et al 2011). The good prospects presented by the application of ISSR and SSR markers to assess the diversity in Coffea have led to this study.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers allow direct access to the genome sequences and, thus, isolate the genetic variation of the environmental interferences (Ferrão et al 2007). The potential use of the Simple Sequence Repeats (SSR) and Inter-Simple Sequence Repeats (ISSR), microsatellite primers, has been demonstrated for Coffea related with genetic diversity of native species and germplasm bank accessions, geographical origin detection, domestication degree, coffee plant dispersion history, species identification and genealogy (Masumbuko and Bryngelsson 2006;LopezGartner et al 2009;Tshilenge et al 2009;Missio et al 2010;Setotaw et al 2010;Mishra et al 2011). The good prospects presented by the application of ISSR and SSR markers to assess the diversity in Coffea have led to this study.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of molecular markers, such as restriction fragment length polymorphism (RFLP), random amplified polymorphic DNA (RAPD), amplified fragment length polymorphism (AFLP), inter-simple sequence repeat (ISSR), simple sequence repeats (SSR), and expressed sequence tag derived simple sequence repeats (EST-SSR) have been used in coffee genetic diversity studies (Combes et al 2000;Steger et al 2002;Diniz et al 2005;Maluf et al 2005;Missio et al 2010;Mishra et al 2011). Tornincasa et al (2006 made a comparative analysis between the commercial coffee cultivars of American, Indian, and African origin and expressed that Indian cultivars were genetically diverse from the American and African cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…A tetraploid species like arabica has different "copies" which tend to be less similar while the algorithms and software developed for assembly were mainly developed for haploid or diploid genomes may lead to the risk of information loss when using it for genome assembly in polyploid crops (Margarido and Heckerman, 2015). Since arabica is an allotetraploid crop, it is expected to show heterozygosity conditioned by two different alleles derived from two different progenitors (Mishra et al, 2011). Paralogous regions and heterozygous sites create "bubbles" during genome assembly where two or more regions that are highly similar assemble together, and the adjacent dissimilar regions assemble separately but eventually merge again (Michael and VanBuren, 2015) make it hard for assembly.…”
Section: A Draft Genome Assembled Using Both Illumina and Pacbio Readsmentioning
confidence: 99%
“…However, due to its allotetraploid origin, C. arabica contains a considerable amount of fixed heterozygosity and shows high levels of heterozygosity at individual loci (Lashermes et al, 1999). Similarly, Mishra et al (2011) suggested that since arabica is an allotetraploid crop, it is expected to show heterozygosity conditioned by two different alleles derived from two different progenitors. Heterozygosity within the two ancestral genomes appears to have been lost, since only one allele from each genome remains in arabica, indicating a possible lack of recombination between the ancestral genomes, while recombination within each genome occurs normally (Cubry et al, 2008).…”
Section: Snp Detection Using CC and Ce Genomes As Referencementioning
confidence: 99%